2019
DOI: 10.1111/mpp.12792
|View full text |Cite
|
Sign up to set email alerts
|

Nicotiana species as surrogate host for studying the pathogenicity of Acidovorax citrulli, the causal agent of bacterial fruit blotch of cucurbits

Abstract: Summary Bacterial fruit blotch (BFB) caused by Acidovorax citrulli is one of the most important bacterial diseases of cucurbits worldwide. However, the mechanisms associated with A. citrulli pathogenicity and genetics of host resistance have not been extensively investigated. We idenitfied Nicotiana benthamiana and Nicotiana tabacum as surrogate hosts for studying A. citrulli pathogenicity and non‐host resistance triggered by type III secreted (T3S) effectors. Two A. citrulli strains, M6 and AAC00‐1, that repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 58 publications
(86 reference statements)
2
33
0
Order By: Relevance
“…Similar to most plant pathogenic bacteria, Ac uses the type III secretion system (T3SS) to inject type III effector (T3E) proteins into the host to cause disease (Jimenez-Guerrero et al, 2020). However, unlike other well-studied T3SS-dependent pathogenic bacteria, how T3Es perturb innate plant immunity remains mostly unknown for Ac (Traore et al, 2019;Jimenez-Guerrero et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to most plant pathogenic bacteria, Ac uses the type III secretion system (T3SS) to inject type III effector (T3E) proteins into the host to cause disease (Jimenez-Guerrero et al, 2020). However, unlike other well-studied T3SS-dependent pathogenic bacteria, how T3Es perturb innate plant immunity remains mostly unknown for Ac (Traore et al, 2019;Jimenez-Guerrero et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To assess this hypothesis, we first carried out inoculation experiments of melon and Nicotiana benthamiana leaves using the syringe infiltration method. N. benthamiana was included in these assays since it was recently shown that this plant can be used as a surrogate host for studying pathogenicity aspects of A. citrulli (Traore et al, 2019). These experiments showed no differences in the progress of symptom appearance and in symptom severity among the tested cured strains, non-cured strains and wild-type M6 (Figure 5A and Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, it was found that the YopJ homologous protein from A. citrulli Aac5 induced PCD symptoms [ 17 ]. Traore et al [ 16 ] also reported that the YopJ homologous protein from A. citrulli AAC00-1 induced PCD symptoms in N. benthamiana . ROS burst is a key event in the PTI response [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three putative effectors of A. citrulli were found to induce PCD in N. benthamiana leaves. Among them, A. citrulli strains M6 and AAC00-1 mutated in the Aave_1548 effector gene and displayed reduced virulence in N. benthamiana [ 16 ], which was the first detailed report of a putative PCD-inducing effector in A. citrulli . In a previous study, we found that the YopJ homologous effectors in A. citrulli Aac5 strain also induced PCD in N. benthamiana [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation